2002
DOI: 10.1038/sj.bmt.1703335
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by cyclosporine A and tacrolimus of serotonin-induced formation of small platelet aggregation

Abstract: Summary:Cyclosporine A (CsA) may increase the incidence of thrombotic events, but whether tacrolimus (Tc) has such effects is still unclear. The serotonergic system has been linked to the thrombotic effects of CsA, but a direct effect of CsA on serotonin-induced platelet aggregation has not been demonstrated because of methodological difficulties. We measured the effects of CsA and Tc on serotonin-induced platelet aggregate formation by particle counting using light scattering. CsA and Tc both enhanced seroton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Therefore, it seems unlikely that this change in immunosuppression over time can explain reduced pancreatic enzyme levels in AT patients. Furthermore, a comparable procoagulant effect has been shown for both CsA and FK through the release of endothelin (29) and serotonin-induced platelet aggregation (30).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Therefore, it seems unlikely that this change in immunosuppression over time can explain reduced pancreatic enzyme levels in AT patients. Furthermore, a comparable procoagulant effect has been shown for both CsA and FK through the release of endothelin (29) and serotonin-induced platelet aggregation (30).…”
Section: Discussionmentioning
confidence: 80%
“…First, the number of patients is clearly limited. Furthermore, a comparable procoagulant effect has been shown for both CsA and FK through the release of endothelin (29) and serotonin-induced platelet aggregation (30). The field of pancreas transplantation has without doubt evolved over the study period.…”
Section: Discussionmentioning
confidence: 97%
“…We have also previously reported that capillary endothelial damage related to cyclic GMP occurred in patients receiving total body irradiation, but not in patients who did not receive it (17). Furthermore, we have found that both cyclosporine A and FK506 caused vascular endothelial damage, with that due to FK506 being more severe (18), and that infection with cytomegalovirus or human herpesvirus‐6 caused direct vascular endothelial injury (19). In addition, we have reported that the levels of P‐selectin, von Willebrand factor antigen, and thrombomodulin are significantly increased in patients who develop neurologic symptoms (20), that a transient increase of IL‐12 occurs in association with recovery of the white blood cell count (7), and that IL‐8 is closely associated with the development of TTP/HUS (8).…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms may be of benefit to patients with COVID-19. Indeed, there is clinical evidence that CsA and tacrolimus are beneficial for COVID-19 patients [92] , [94] ; however, patients with COVID-19 often have accompanying hypertension and hypercoagulable state, due to the compensatory increase in angiotensin II and CNI can cause high blood pressure and thrombosis as side effects [95] , [96] , emphasizing the need to monitor blood pressure when treating patients with SLE and COVID-19, and to consider the safety of CNI in cases with hypertension or hypercoagulable state occurs. Nevertheless, due to the strong immunosuppressive function of CsA and tacrolimus, alisporivir, a non-immune substitute molecule for CsA, may be a better choice.…”
Section: Calcineurin Inhibitormentioning
confidence: 99%